Development of Social Business Model in the Green Creative Industry Sector: A Study on Boolenial Enterprises - Nurulita, Vica Widiyana; Nurfitriya, Mira; Rachmani, Nizza Nadya (A Social Science and Entrepreneurship Journal, 2021)
The development of the creative industry is not optimal, this is due to the lack of attractiveness of the industry, the dominant position of creative businesses, the immature creative industry business model and the lack of guidance from the government, as well as the business risks that must be faced. This research uses a case study method so that a causal explanation of the conditions in the field can be produced and can answer the "how" and "why" questions so that comprehensive study results can be obtained and can answer the problems that arise in this research. Data was collected by means of literature studies and interviews. The data analysis process is carried out by describing the business through the Social Business Model Canvas (SBMC), and exploring the insights of the social business model with the middleman model.